Psychometric properties of the depression anxiety stress scale 21-item (DASS-21) Malay version among a big sample population of Non-Malays in Malaysia - Musa, Ramli; Mohammad Aidid, Edre (Malaysian Psychiatric Association, 2020)
Introduction: The Malay version of Depression Anxiety Stress Scale 21-item (M-DASS-21) has been tested in various populations in Malaysia. We are interested to look at the psychometric properties of the M-DASS-21 among Non-Malays in Malaysia. Objectives: This study aimed to analyse its psychometric values among non-Malays based on a big sample size. The analysis was based on Exploratory Factor Analysis and construct validity.